(untitled) (Journal of Medical & Health Sciences Review, 2025)
The homes of regular animals are often destroyed by humans for unusual reasons, which can be really bad for the variety of life that follows the rules of nature. The number of endangered species in many areas is still unknown because there aren’t enough animal populations. In certain places, it’s really important to keep records of the animals in the area to help protect them better. We collected data by counting animals along straight lines and paths. In our study, we found a total of fifteen species from twelve different families, spread across five different groups of animals. In the reported species belong to five order which are Artiodactyla with one family Suidae, Carnivora with three families canidae,felidae and herpestidae, Rodentia with three familes i.e sciuridae,Muridae Hystricidae , Eulipotyphla ,are represented by soricidae,liporidae Canidae families while chiropterais represented by vespertilionidae family,Similarly the species observed in the reported areas are Golden jacka Canus aureus l,red fox Vulpes vulpes grey mangoose Herpestes edwardsii, porcupine Hystrix indica ,plam squirrel Funambulus pennantii,house mouse Mus musculus,black house rat Ratus rattus, Asian house rat Rattus taezumi house shrew Suncus murinus,wild Rabbit Lepus nigricollis, indian flying fox or fruit bat Pteropus medius . The wild boar, known as Sus scrofa, has become the most dominant and commonly found animal in the area. Four different groups of animals are protected under the Khyber Pakhtunkhwa flora and fauna law from 2015. The animals are under pressure due to human activities and face various threats. In order to resolve conservation problems and ensure long-term sustainability of regional animal populations, one must ensure multidisciplinary integration of research projects. It is these issues that need to be dealt with profitably with the participation of the ecologists, zoologists, conservationists and the policy makers.